ncRNAs-mediated high expression of TICRR promotes tumor cell proliferation and migration and is correlated with poor prognosis and tumor immune infiltration of hepatocellular carcinoma - Ke-Jie He; Yang-fan Zhang; Lai-ying Liang; Xiao-Shen Cheng; Guoyu Gong; Xiao-Mei Ouyang; Ying Lin; Bayasi Guleng (Elsevier, 2022)
TICRR is a regulatory factor of DNA replication with ToPBP1 interaction. At present, the underlying function and mechanisms of TICRR remain unclear in LIHC. Our objective was to assess the function and prognosis of TICRR in LIHC. We conducted a differential expression analysis, GO/KEGG, and GSEA enrichment analysis of TICRR in LIHC. We also carried out the gene frequency and SCNA of TICRR. We found that TICRR could serve as an independent prognostic marker in LIHC by univariate and multivariate analysis. In addition, we observed that TICRR was related to immune infiltration, and TICRR had positive correlation with PD1/PD-L1 and CTLA-4 in LIHC. The hsa-miR-126-3p/IPO9-AS1 may be the candidate ncRNAs to regulate the expression of TICRR. The high rate of SCNV of TICRR might have critical effect on the function of CTL cells in LIHC. We further demonstrate through a series of experiments that TICRR facilitated the proliferation and metastasis of liver cancer cells in vitro. Altogether, TICRR might be a potential biomarker and therapeutic target in LIHC.